Variables Associated With Successful Treatment Outcomes of Autistic Youth Enrolled in PEERS - McLeod, Justin W. H.; McCrimmon, Adam W. (Frontiers in Psychiatry, 2022)
This study sought to examine how certain variables of autistic youth who completed a formal social intervention program (PEERS) predicted social skill improvement post intervention. Specifically, this research aimed to determine if age, gender, emotional intelligence, intellectual ability, and/or autism symptomatology predicted social skill outcomes. Using extant data from parent and self-report batteries, change scores and multiple regressions were employed to examine which variables accounted for social skill improvement. Only intellectual ability (FSIQ), specifically perceptual reasoning, significantly predicted social skill outcomes based upon teen self-report, suggesting that autistic youth with specific cognitive profiles may be benefit more from PEERS. This research also exemplifies the heterogeneous nature of autism symptomology and the continued need for research examining social skill interventions. Limitations and future directions are discussed.